Assessment of Ecosystem Health and Carbon Stocks in the Seagrass Meadows of Mengiat Beach, Bali, Indonesia - Choesin, Devi Nandita; Gouw, Amadeus Devin; Pitriana, Pipit (Marine Science Department Diponegoro University, 2024)
Seagrass meadows provide many important ecosystem services. They are now recognized as blue carbon ecosystems that are crucial in the mitigation of global climate change. This study was conducted at Mengiat Beach in Bali, Indonesia, where there are extensive seagrass meadows along the shorelines, but also considerable anthropogenic activity that pose threats to the ecosystem. The objectives of this study were to: (1) describe the seagrass community at Mengiat Beach; (2) assess the health status of the seagrass ecosystem; and (3) estimate carbon stocks stored within the ecosystem. Vegetation analysis was conducted to describe the seagrass community in terms of density, cover, biomass and species importance. Spatial Sentinel-2 satellite data with unsupervised classification was used to determine the extent of seagrass meadows. Carbon stocks in sediment and biomass were estimated using the loss on ignition method. The seagrass community at Mengiat Beach consists of at least five different species, dominated by Cymodocea rotundata. The meadows are characterized by high density (588 ind.m-2) and good cover (60.7%). They are considered healthy, with good ecological quality, as indicated by a SEQI (Seagrass Ecological Quality Index) of 0.69. The seagrass ecosystem stores a significant amount of carbon, with 99.23% of it stored in sediment. Total carbon stock in sediment and seagrass biomass is estimated at 133.39 MgC.ha-1. When extrapolated to the total seagrass area of 43.21 ha, the meadows at Mengiat Beach store a total carbon stock of 5.76 GgC, highlighting their potential as high-carbon reservoirs and importance in climate change mitigation efforts.